Association of ocular biometric parameters with diabetic retinopathy - Utaal, Shubhneek Kaur Dhillon; Chopra, Rupali; Batra, Nitin (International Journal of Research in Medical Sciences, 2020)
Background: To study the association of ocular biometric parameters Spherical equivalent (SE), Axial length (AL), Anterior chamber depth (ACD) and Corneal curvature (CC) with diabetic retinopathy (DR) in subjects with Type 2 diabetes mellitus (DM). Methods: This prospective observational study was conducted in the Outpatient Department of Ophthalmology of a tertiary care teaching hospital in North India. The study included 100 subjects having various grades of DR as cases and 100 diabetics without DR as controls. The SE was assessed using objective autorefraction, while AL, CC and ACD were measured using the NIDEK AL SCAN. International Clinical Diabetic Retinopathy Disease Severity Scale was used for grading of DR. Results: A total of 181 eyes in the study group and 200 eyes in the control group were analysed. Progressive decrease in the mean AL was observed with the increasing severity of DR (p=0.017). Deeper ACD had a negative correlation with severity of DR (p=0.037). No statistically significant difference was observed for AL and ACD with the incidence of DR (p=0.147 and p=0.091 respectively). Likewise, there was no significant relation of DR with SE or CC. Conclusions: Longer AL and deep ACD were protective against progression to the severe forms of DR. However, there was no correlation of AL and ACD with the incidence of DR. The SE and CC were not found to be significant determinants for either development or severity of DR.